Good Agriculture Practices (GAP) Tanaman Kopi Menghasilkan Tahun 1 dan 2 - Ghufron Rosyady, Muhammad; Wulanjari, Distiana; Alit Farisi, Oria; Burhanuddin Irsyadi, Muhammad; Anom Wijaya, Ketut (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
Curahpoh Village, Curahdami District, Bondowoso Regency is able to produce quality coffee and can be used as a coffee center village. The economy of the people there depends on the harvest from coffee plantations. Coaching started from 2019 until now and continues to be carried out. The coffee farmers we train are coffee farmers who are members of LMDH Argo Santoso, Curahpoh Village, Curahdami District, Bondowoso. In 2019, we donated 300 seeds of clones BP 936, BP 939 and BP 409. In 2020, we donated 500 seeds of clones BP 358, BP42 and BP 409. The seeds we donated were superior seeds resulting from grafting technology with BP rootstock. 308. BP 308 is a special coffee plant for rootstock because of its dense and strong roots. The current condition of the coffee plants is that they are grown and cared for well. The service team together with students calculated the production potential of coffee berries. The main parameters in calculating production potential are the effective number of branches, number of dompolans, number of perdompolan fruit and weight per coffee fruit. The calculation results of the potential production of coffee grown from the grant are 2.1 tons/ha. The production potential reaches 6 times the potential of coffee owned by farmers in Curahpoh, which is around only 0.4 tons/ha.